Tea seed oil: Physicochemical profiling - Patel, Pradeep Kumar; Sarma, Rupak; Das, Buddhadeb; Singh, Shobhit Kumar; Barooah, Anoop Kumar (Journal of Plantation Crops, 2020)
A study was undertaken to evaluate the quality characteristic of tea (Camellia sinensis L.) seed oil. The oil content ranged between 20.84 and 21.90 per cent. Smoke point, iodine value, saponification value, calorific value, refractive index, oil density, oil colour and oil pH were in the range of 247.29 - 251.53 (oC), 82.74 - 85.65 (g I 100-1 g), 185.33 - 185.72 (mg KOH g-1), 6822.53-6891.05 (J per 100 g), 1.46 (at 40 0C), 0.92 - 0.94 (g per cm3), 4.45 - 4.47 (Y+5R) and 4.62 - 4.64, respectively. The oxidation parameters, i.e., peroxide value, ranged from 1.17 - 2.63 meq kg-1. The tea seed oil has PUFA/SFA ratio 0.82 - 1.31 closer to WHO recommended value. Besides, antioxidant activity in term of DPPH free radical scavenging activity ranged between 6.30 - 7.14 per cent, β-carotene 4.62 - 12.93 mg kg-1 and α-tocopherol 90.49 - 366.52 mg kg-1. Highest oleic acid content was found in TSS 1, whereas highest α-tocopherol was found in TS 557. The results open up the possibilities of extracting oil from these bi-clonal seed stocks, which will diversify the use of tea.